A wolf in sheep's clothing—aortic stenosis and cardiac amyloidosis: “RAISE”ing awareness in clinical practice - Sabbour, H.; Al-Humood, K.; Al Taha, Z.; Romany, I.; Haddadin, H.; Mohty, D. (Frontiers in Cardiovascular Medicine, 2024)
Aesop's fable of the wolf in sheep's clothing encourages us to look beneath the exterior appearance of a situation and evaluate the truth that lies beneath. This concept should be applied when managing older patients with severe aortic stenosis. This population of patients are increasingly being identified as having concomitant cardiac amyloidosis, which is an underrecognized cause of common cardiac conditions. The presence of cardiac amyloidosis negatively affects the outcome of patients with aortic stenosis, these patients are undergoing transcatheter aortic valve replacement (TAVR) with increasing frequency and have a significantly higher overall mortality rate than patients with aortic stenosis alone.Although left ventricular wall hypertrophy is expected in patients with aortic stenosis, it should not be assumed to be due only to aortic stenosis, suspicion of cardiac amyloidosis should be raised in patients where the degree of hypertrophy is disproportionate to the degree of aortic stenosis severity. The RAISE score was developed to predict the presence of cardiac amyloidosis in patients with severe aortic stenosis. This article highlights the value of increased clinical suspicion, demonstrates the use of the multiparameter RAISE score in daily clinical practice, and illustrates the scoring system with case studies. In elderly patients being considered for TAVR, the systematic testing for cardiac amyloidosis should be considered as part of the pre-operative work-up.